2017
DOI: 10.5897/ajb2017.16107
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating chemical composition of Butia capitata pulp among various populations and locations using multivariate analysis

Abstract: There are many native species from Cerrado that are used as food supply. However, their nutritional constitution is still unknown. The objective of this study was to evaluate and quantify the nutritional composition of coquinho-azedo fruits, obtained from different regions and populations in Northern Minas Gerais, using multivariate analysis. Ripe fruits of various B. capitata populations were obtained from four locations in Northern Minas Gerais. Fruit samples were analyzed for total acidity, total sugars, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The extracts were prepared using 1.0 g of fresh leaves and the methodology proposed by Magalhães et al (2017). Free radical scavenging activity of different extracts of C. longa shoots were measured using 2,2-diphenyl-1-picrylhydrazyl (DPPH) (Rufino et al, 2009).…”
Section: Measurement Of Antioxidant Activity By the Dpph Methodsmentioning
confidence: 99%
“…The extracts were prepared using 1.0 g of fresh leaves and the methodology proposed by Magalhães et al (2017). Free radical scavenging activity of different extracts of C. longa shoots were measured using 2,2-diphenyl-1-picrylhydrazyl (DPPH) (Rufino et al, 2009).…”
Section: Measurement Of Antioxidant Activity By the Dpph Methodsmentioning
confidence: 99%
“…The variability between the results of the present study and those observed by other authors may be due to differences in the environmental, soil and climatic conditions of the fruit collection sites, as well as the population of plants analyzed. In a recent study, it was verified that the content of some micronutrients and bioactive compounds of Butia capitata varied according to these parameters (Magalhães et al, 2017). It should also be considered that the collected fruits had spontaneous growth, without antropic action in the growing conditions which can provide a natural variability among the samples.…”
Section: Centesimal Compositionmentioning
confidence: 97%